Strong subjectivism in the Marxian theory of exploitation: A critique - Roberto Veneziani; Naoki Yoshihara (Queen Mary University of London, Department of Economics, 2009)
This paper critically analyses the strongly subjectivist approach to exploitation theory recently proposed by Matsuo ([7]), in the context of general convex economies with heterogeneous agents. It is proved that the Fundamental Marxian Theorem is not preserved in his subjectivist approach, contrary to Matsuo's claims, and that no meaningful subjectivist exploitation index can be constructed. It is argued that a minimal objectivism is necessary in exploitation theory, whereby subjective preferences do not play a direct, definitional role. An alternative objectivist approach is briefly analysed, which is related to the 'New Interpretation' ([1]; [3]). It is argued that it captures the core intuitions of exploitation theory and it provides appropriate indices of individual and aggregate exploitation. Further, it is shown that it preserves the FMT in general economies.
Keywords: D31; D46; D63; E11; B51; 330; exploitation; subjective preferences; Fundamental Marxian Theorem; general convex cone economies; Marxistische Arbeitstheorie; Werttheorie; Sozialistische Wirtschaftstheorie; Eigeninteresse; Kritik; Theorie